PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI MELALUI MEDIA VIDEO TERHADAP PENGETAHUAN REMAJA LAKI-LAKI TENTANG DAMPAK SEKS BEBAS - Novi Wulansari; Trisya Mutiara (Maternal Child Health Care, 2021)
The problems of adolescents in Indonesia are getting more concerning. Due to the lack of knowledge on reproduction and correct sexuality, many teenagers actively engaged in premarital sexual intercourse. The purpose of this study was to determine The Effect of Reproductive Health Education through Video Media on Adolescent Boys Knowledge about the Impact of Free Sex at SMK Humaniora in Kerinci Regency in 2020. The of this study was experimental method with one group pretest-posttest Design. The population was all students of SMK Humaniora. They were 64 students.By usingpurposive sampling technique, 20 students were chosen as the samples. The instrument was a questionnaire.The results of the research before being given reproductive health education with an average of 32.30, the average after being given reproductive health education was 44.45 and the statistical test found a p-value of 0.005, which means that Ha is accepted.It was concluded that there were differences in the level of knowledge of students before and after being given reproductive health education about the impact of free sex at SMK Humaniora, Kerinci Regency in 2021. It is hoped that students increase knowledge of reproductive health, especially about free sex.Keywords               : Free Sex, Knowledge, Adolescents References    : 36 (2010-2020)